Bridging the Capabilities–Expectations Gap: Lessons Learned from Post-Conflict Democracy Assistance to Liberia. Issue 3 (3rd July 2019) - Lappin, Richard
ABSTRACT: The unfulfilled expectations of post-conflict democracy assistance are palpable and disconcerting. The backsliding of several post-conflict states from democracy to authoritarianism, or even to violent conflict, has prompted a serious revision of the merits of democracy assistance. The lack of engagement with the very values and assumptions attached to democracy assistance can precipitate a debilitating gap between what assistance is capable of accomplishing through its strategic instruments and what people and partner organizations expect and demand assistance to deliver in post-conflict countries. Positively, the practice of post-conflict democracy assistance is responding to these challenges, showing signs of maturity and sophistication. The case of Liberia demonstrates that enhanced financial resources, improved peacekeeping, a broader conception of democracy, and a more refined use of instruments can bridge the capabilities–expectations gap on critical themes. Gaps, however, remain, including the conflation of democracy building and peacebuilding, unrealistic expectations of the benefits of democracy aid, and the often-exaggerated importance that international organizations proclaim for their work. These gaps ought to be addressed as they may not only undermine the successes and credibility of peacebuilding, but also shatter the hopes of local citizens who believe that international involvement will help them achieve democracy and peace.